Predictive factors and prognostic value of pathologic complete response of ipsilateral supraclavicular lymph nodes in breast cancer after neoadjuvant chemotherapy - Zhu, Jiujun (Ann Transl Med, 2019)
BACKGROUND: Breast cancer with ipsilateral supraclavicular lymph node metastasis is one of the indicators of poor prognosis. Patients who attain pathologic complete response in breast and axillary sites have improved survival and are highest in aggressive HR–HER2– and HER2-positive tumor subtypes. However, there is no study on the related factors and prognostic value of supraclavicular pathologic complete response in breast cancer after neoadjuvant chemotherapy. The aim of our work was to investigate the factors and prognostic significance of pathologic complete response of ipsilateral supraclavicular lymph node metastasis in breast cancer after neoadjuvant chemotherapy. METHODS: A total of 214 patients with breast cancer who had primary ISLN metastasis, receiving NAC and subsequent ISLN dissection, were retrospectively and consecutively reviewed. Univariate and multivariate analyses were performed using χ(2) test and the logistic regression model, and the prognosis was analyzed by Kaplan-Meier curve. RESULTS: All patients included were women who were 26–74 years old. The rate of supraclavicular pathologic complete response (pCR) was 53.7%. Multivariate analysis showed that the expression of Ki67, breast pCR, and axillary pCR were independent predictors of supraclavicular pCR (P<0.05). After a median follow-up of 16.2 months, the risk of recurrence and metastasis in patients with supraclavicular pCR was half reduced compared to that of the non-pCR group (HR 0.51, 95% CI, 0.32–0.80, P<0.01), mainly manifested in HR–HER2– and HER2-positive disease. CONCLUSIONS: The expression level of Ki67, breast pCR, and axillary pCR were independent predictors of supraclavicular pCR. Supraclavicular pCR was an independent predictor of disease-free survival (DFS). Surgical removal of supraclavicular lymph nodes can accurately evaluate the rate of supraclavicular pCR, which is of great significance for patient prognosis.